Guardians under Fire: Unveiling Violence on Emergency Healthcare Professionals: A Multicenter Questionnaire Based Cross Sectional Survey - HUMA NASIR,; PATRICIA C. MENDES,; ALAM SAWWA,; IMRAN ALI,; ASIF HASSAN,; MUHAMMAD ARSLAN ZAHID, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: It focuses to identify the factors related to workplace violence who, what and where and to evaluate the knowledge of reporting among healthcare staff. Aim: To establish the common types of workplace violence that health care workers in emergency departments of tertiary care hospitals in Pakistan are vulnerable to. Methodology: Cross-sectional research study methodology was adopted in this study in assessing the proportion of healthcare practitioners who encounter workplace violence. The study was carried out in the emergency facilities in tertiary care hospitals in Pakistan, from March 2023 to August 2023. The 383 emergency department healthcare professionals who had worked for at least 6 months were surveyed for the study. Due to the pilot nature of the study and to increase participation, the questionnaire was made available online, though participants orally assented to the study. Mean scores and standard deviations were used to describe the variables while independent samples t-tests, one-way analysis of variance (ANOVA) and logistic regression analysis were used to determine the differences, relationships and risk factors respectively. Results: The survey revealed that 87.5% of doctors, nurses and other healthcare personnel accounting to workplace violence stated that had suffered verbal abuse at the workplace. Physical assault was 5.0%, bullying or mobbing 5.2% and sexual harassment only 0.5%. Similarly, health care workers that are male and those with more than a decade of practice in the profession were more vulnerable to violence with odds ratios of 1.37 and 2.25 respectively. As for the reporting behavior, it was not very high – 28.7% of participants reported actual incidents of violence at work. Conclusion: Emergency staff experience workplace violence in the workplace and verbal aggression is the most prevalent type of violence. Experience for more than five years, work place setting and male gender emerged as antecedents to predicting workplace violence. The safety of the health care professional and increased safety for the patient requires attempts to be made to better a situation and to enrich a reportage process. Keywords: Workplace violence, emergency healthcare, verbal abuse, cross-sectional survey, reporting behavior.